Researching Dynamic Capacities of Restaurants for Creating Customer Value in Conditions of Digital Transformation - M. Yu. Helal; T. F. Palei (Вестник Российского экономического университета имени Г. В. Плеханова, 2023)
Digital transformation is a way to increase value for guests in restaurant business. Thanks to it, restaurants can provide their guests with more personalized services. Moreover, digital transformation helps restaurants become more efficient and save money and at the same time it gives more opportunities and better service to customers, improves marketing strategies and attracts more guests. The goal of the research is to estimate dynamic capacities of restaurants for creating customer values in conditions of digital transformation. The research studies three dynamic capacities of digital probing: digital surveillance, digital scenario planning and shaping digital thinking. Digital surveillance helps restaurants find potential opportunities for digital transformation and develop strategies, which can provide profits from these opportunities. Digital scenario planning helps restaurants plan potential results of digital transformation and develop strategies, which can provide profits from potential opportunities and reduce potential risks. Shaping digital thinking helps restaurant owners, managers and employees develop necessary culture in order to implement changes and introduce innovation. Thus, the research can enrich the theoretical foundation of the sector of tourism and hospitality. The proposed three dynamic capacities can be used to realize opportunities of digital transformation for creating values for customers. In practice the research shows how restaurants can use existing opportunities.